Hepatic arteriovenous fistula of traumatic origin - Valls, Alberto; Perdomo, Roberto; Balboa, Oscar; Melogno, Silvio; Boschi, Jorge; Chiossoni, Marta (Cirugía del Uruguay, 1974)
Traumatisms, wounds and contusions of liver may give rise to holes in arterial vessels of varying importance, of branches of the portal vein and of biliary duet within the hepatic parenchima. Under such circumstances traumatic arteriovenous fistulas may occur and in turn, lead to portal hypertension ( and ascitis in sone cases), hemobilia and hepatic lesions (ischemic, infections or obstruction of biliary ducts), hese may explain hepatic cholics and deterioration of general condition of patients, leading to the patient's death as consequence of these disorders or of hemobilia. Selective arteriography permits diagnosis of this condition which is Hable to occur in any import¡nt !ver traumatism. .Surgery is employed to interrupt communication of this fistula, often through ligature of corresponding arterial or venous vessels and resection of the hepatic territory tributary to such vessels; less frequently through suture of communication preserving vascular integrity.